ANALISIS JARAK JANGKAUAN LORA DENGAN PARAMETER RSSI DAN PACKET LOSS PADA AREA URBAN - Yanziah, Asma; Soim, Sopian; Rose, Martinus Mujur (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
Low Power Wide Area Networks (LPWAN) is a wireless communication technology that supports the development of the Internet of Things (IoT). LPWAN offers a wider coverage area and low energy consumption. LoRa is one of the most popular LPWAN technologies. LoRa technology is suitable for IoT application scenarios that only need to send small amounts of data over long distances and low-power transmission data. This research focuses on testing the range of the LoRa Rfm 95/96 chip at 920 MHz and SF7 frequencies for urban areas. The parameters used are Received Signal Strength Indicator (RSSI) and Packet loss. RSSI test results will be compared with RSSI calculation results using the log normal shadowing model. The RSSI value of the test results is closer to the calculation of the RSSI value for the free space area with the addition of a shadowing effect. When viewed from the range of RSSI values ​​at each test point, RSSI is relatively stable. However, based on RSSI average testing and calculation, RSSI has decreased while packet loss has increased with each additional distance. From this study, the maximum LoRa range is 2 km. This is in line with LoRa specifications for urban areas.